Improvement of e-commerce recommendation systems with deep hybrid collaborative filtering with content: A case study - Wójcik, Filip; Górnik, Michał (Wykorzystanie Hybrydowych Głębokich Sieci Neuronowych jako systemów rekomendacyjnych. Studium przypadku, 2020)
This paper presents a proposition to utilize flexible neural network architecture called Deep Hybrid Collaborative Filtering with Content (DHCF) as a product recommendation engine. Its main goal is to provide better shopping suggestions for customers on the e-commerce platform. The system was tested on 2018 Amazon Reviews Dataset, using repeated cross validation and compared with other approaches: collaborative filtering (CF) and deep collaborative filtering (DCF) in terms of mean squared error (MSE), mean absolute error (MAE) and mean absolute percentage error (MAPE). DCF and DHCF were proved to be significantly better than the CF. DHCF proved to be better than DCF in terms of MAE and MAPE, it also scored the best on separate test data. The significance of the differences was checked by means of a Friedman test, followed by post-hoc comparisons to control p-value. The experiment shows that DHCF can outperform other approaches considered in the study, with more robust scores
Econometrics = Ekonometria, 2020, Vol. 24, No. 3, s. 37-50
Keywords: collaborative filtering; deep learning; content model; product recommendation; filtracja kolaboratywna; głębokie uczenie; model treści; rekomendacja produktu